2016
DOI: 10.1016/j.jhydrol.2016.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating soil evaporation parameterizations at near-instantaneous scales using surface dryness indices

Abstract: a b s t r a c tSoil evaporation is an important component in the water and energy cycles on land, especially for areas that are moderately or densely covered by bare soil. Soil evaporation parameterizations that scale down potential evaporation with the soil surface temperature (T s ) and/or the air humidity are regionally applicable because of the advantage of omitting pixel-scale near-surface soil moisture. In this paper, we provide an intercomparison study among these parameterizations. Potential evaporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The PT equation has also served as a core part of many of the evapotranspiration models (Gan et al, 2019; Gan & Gao, 2015; Gao et al, 2016; Garcia et al, 2013; Liu, Hiyama, et al, 2012). Before the work of Priestley and Taylor (1972), Penman (1948) had derived an equation that describes the joint control of energy supply and heat transport on the evaporation of water bodies, as shown in Equation .…”
Section: Methodsmentioning
confidence: 99%
“…The PT equation has also served as a core part of many of the evapotranspiration models (Gan et al, 2019; Gan & Gao, 2015; Gao et al, 2016; Garcia et al, 2013; Liu, Hiyama, et al, 2012). Before the work of Priestley and Taylor (1972), Penman (1948) had derived an equation that describes the joint control of energy supply and heat transport on the evaporation of water bodies, as shown in Equation .…”
Section: Methodsmentioning
confidence: 99%
“…In G c -TSEB, the latent heat flux of the soil layer is calculated based on the complementary concept, expressed as the product of potential evaporation ( , W/m 2 ) and relative 𝐿𝐸 𝑠_𝑃𝑀 evaporative fraction ( ) (Gan et al, 2019;Gao et al, 2016), instead of mass transfer and soil 𝑓 𝑝 moisture (Kustas et al, 1998).…”
Section: 𝛼 𝐺mentioning
confidence: 99%
“…Kustas et al (2003), Li et al (2006) and Li et al (2019c) suggested the parameterizations for vegetation and soil in flux estimations are worth of attention. Considering the inaccessibility of global soil moisture at fine temporal-spatial resolution (Ahlmer et al, 2018) and the decoupling between the water content in the upper and deeper soil layers (Capehart and Carlson, 1997;Carranza et al, 2018), Gan et al (2019) revised the G c -TSEB to derive soil evaporation relying on the complementary concept and surface dryness index (SDI) (Gao et al, 2016), instead of the original TSEB scheme requiring soil moisture content as model input (Kustas et al, 1998). The difference in the result of model simulations for the combination of the new biophysical constraints and the two soil evaporation schemes can tell us something about vegetation functions and model capabilities of ET estimation and partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…The Priestley-Taylor equation [18] has been widely used as a stand-alone model [45] or as a core part in many ET models [46][47][48][49][50]. The remarkable changes in the water level of Poyang Lake provide a unique opportunity for comparatively studying the variations in α and their controlling factors over water-covered and non-water-covered surfaces.…”
Section: Use Of the Pt Equation In Changing Surface Conditionsmentioning
confidence: 99%